KEDUDUKAN NEGARA SEBAGAI PENGELOLA WARISAN ATAS HARTA PENINGGALAN TAK TERURUS MENURUT SISTEM WARIS BURGERLIJK WETBOEK - Oemar Moechthar (Yuridika, 2017)
The legal system of inheritance in Indonesia is divided into three systems, namely western heirs legal system derived from burgerlijk wetboek (hereinafter referred to as "BW"), the legal system of inheritance of Islam derived from the Qur'an, hadith and ijma, and customary inheritance law. Burgerlijk Wetboek inheritance law governing the possible legacy of someone who would fall into the state and controlled by the state. In certain cases the state on an inheritance from the testator if the testator leaves no heir, and wills, so that the legacy of the heir to the legacy categorized as slipshod heritage (onbeheerde nalatenschap). In this case the Orphan’s Court takes its participation to act as the manager of the neglected. The method used in this research is the approach statute and case approach. The study is in the context of the legal approach doctrinal legal research, but did not rule on the legal interpretation methods can be primarily related to the issues to be investigated. Regulation of Orphan’s Court in Indonesia remains sectoral and still former colonial possessions, so that the necessary regulations concerning Orphan’s Court Law form containing tasks, functions, powers, rights and obligations of the institution.